PENGARUH CANGKANG TELUR DAN AIR LIMBAH TEMPE TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA - Kotia, Dina Ferozsah; Setyo Andi Nugroho; Kusuma, Satria Indra; Fatimah, Titien; Novenda, Ika Lia (JURNAL BIOSENSE, 2024)
Indonesia's coffee production in 2020 was 762.38 thousand tons. Coffee productivity in Indonesia can continue to increase with an important breeding process for growing coffee starting from the coffee nursery process. Eggshells can be utilized for planting media because 94% of eggshell content is CaC03, which can stimulate root and stem hair development. Waste from tempeh production can be used as liquid organic fertilizer due to its abundant availability. Tempe waste contains nitrogen (N), phosphorus (P), potassium (K) and other nutrients that can increase plant productivity. The research was conducted with the aim to determine the effect of eggshell planting media and tempeh waste water on the growth of robusta coffee seedlings. The research was conducted in the nursery of seed technology laboratory of Jember State Polytechnic. The results showed that tempe waste water had a significant effect on the growth of robusta coffee seedlings, especially on the stem diameter parameter. In addition, there is an interaction between the composition of eggshell planting media and tempeh wastewater, namely in the parameters of stem diameter and plant dry weight.